ENHANCING A RURAL SCHOOL ENGLISH PROFICIENCY: AN OUTREACH PROGRAM - Ananto, Gigih Dwi; Dewi, Maharani; Habiburrahman , Novan; Iman Jauhari; Agung Hariadi; Gunadi, Lie Epifani Rachmad; Anshori, Ibnu; Rukmono, Indra (Universitas Kristen Cipta Wacana, 2024)
The program is an initiative to improve English language skills among students and educators in rural schools. The background to this program is limited access to effective English language learning in rural areas, which has an impact on students' low English language skills and limited opportunities to compete at a wider level. This program implements interactive, contextual and participatory learning methods, specifically designed to meet learning needs in rural areas. Through various activities such as basic English training, conversation sessions, daily interaction simulations, and teacher involvement in mentoring, this program provides an interesting and applicable learning experience for students. By involving the school community and the surrounding environment, this program is expected to create a sustainable impact, strengthen students' and teachers' confidence in using English, and prepare them for various educational and employment opportunities in the future. The community-based approach in this program not only benefits students, but also empowers educators to adopt more engaging and contextual teaching techniques. Through ongoing evaluation, it is hoped that this program can become an effective English language learning model in rural areas.